Pengaruh latihan dribble 20 yards square dan driblle x pattern terhadap kemampuan dalam permainan sepak bola putra laut selatan kabupaten sumbawa barat usia 10-13 tahun - Zulfikar Mu’min Putra; Lalu Sapta Wijaya Kusuma; Jamaluddin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Focus on problems based on observations during the South Sea Boys training in West Sumbawa Regency, especially the age group of 10-13 years. Many players still dribble the ball using their toes and the distance between their feet and the distance with the ball is too far, so it is easy for opponents to grab. Students are weak in ball possession so that the ball is easily seized by opponents. In dribbling, players still look stiff. There are some players who have speed in running, but when dribbling at high speed, the player is difficult to turn and the ball is too far out of reach. When in possession of the ball, some students tend to control the ball and then dribbling without paying attention to the surrounding area. South Sea Boys players of West Sumbawa Regency, especially the age group of 10 -13 years when running, players have high speed but cannot pass the opponent and the ball is easily grabbed. From the above facts that the dribbling ability must be improved so that the dribbling ability of the players becomes better. Thus, the main problem is the dribbling ability of the South Sea Boys players, West Sumbawa Regency, especially the age group of 10-13 years which is still low. The design used in this study is a type of quantitative research using experimental methods. Experimentation can be interpreted as a research method used to look for the effect of certain treatments on others under controlled conditions. In experimental research there is a treatment (treatment). The sampling technique uses the cumentation method and the deed test method using the help of the IBM SPSS Version 23 program.